2016
DOI: 10.1016/j.crpv.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of bone histology in the extinct elephant bird Aepyornis (Aves, Palaeognathae) from Madagascar

Abstract: a b s t r a c tAepyornis, a giant subfossil ratite from Madagascar, shows a well-preserved bone histology. Hindlimb bones exhibit an extensive histodiversity; the cortex is initially made of fibrolamellar, well-vascularized primary bone that modulates locally into plexiform or laminar patterns. Lines of arrested growth are generally weakly expressed. Haversian reconstruction can be complete. Perimedullar endosteal deposition is variable but can be extensive. The complex causality (phylogenetic, systematic, ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
(53 reference statements)
5
15
0
7
Order By: Relevance
“…Secondary reconstruction was observed in all the skeletal elements, but compared to the femur and the tibiotarsi studied, the tarsometatarsus was the most extensively reconstructed element, with dense Haversian bone tissue present. This finding agrees with [35] that there is a proximodistal gradient in terms of secondary reconstruction with more distal elements being more extensively remodelled. Note that in the aepyornithids, the fibula was the most reconstructed element [5], but in the current study, fibulae were not sampled.…”
Section: Secondary Reconstructionsupporting
confidence: 90%
“…Secondary reconstruction was observed in all the skeletal elements, but compared to the femur and the tibiotarsi studied, the tarsometatarsus was the most extensively reconstructed element, with dense Haversian bone tissue present. This finding agrees with [35] that there is a proximodistal gradient in terms of secondary reconstruction with more distal elements being more extensively remodelled. Note that in the aepyornithids, the fibula was the most reconstructed element [5], but in the current study, fibulae were not sampled.…”
Section: Secondary Reconstructionsupporting
confidence: 90%
“…2012), with the exception of extremely dense Haversian systems present in penguin bones (related to the aquatic lifestyle of these animals (Meister, 1962) and paleognaths (Bourdon et al, 2009;de Ricqlès et al, 2016;Chinsamy et al, 2020a). With respect to the mid-shaft of the humerus and femur, the results of this investigation concur with these studies, and only rare, small, localized areas of osteonal remodeling were observed (e.g., in the wild turkey humerus).…”
Section: Adult Histologysupporting
confidence: 83%
“…At present, it is not clear if the method of textural ageing could be applied to basal birds where the presence of different growth regimes has been suggested by histological studies (e.g., Chinsamy, ; Chinsamy‐Turan, ). A sustained and interrupted growth regime has been reported also in some palaeognathous birds, including Apteryx (Beale, ; Bourdon et al, ), Dinornithiformes (Turvey et al, ; Turvey and Holdaway, 2005), and Aepyornis (de Ricqlès et al, ). It has been found that an apparently smooth surface texture can occur on long bones of immature individuals of Alligator mississippiensis (American alligator) which has cyclical interrupted growth (Tumarkin‐Deratzian et al, ).…”
Section: Discussionmentioning
confidence: 89%